Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport